Site specific identification of endogenous S-nitrosocysteine proteomes - Doulias, Paschalis-Thomas (2013)
Cysteine S-nitrosylation is a post-translational modification regulating protein function and nitric oxide signaling. Herein the selectivity, reproducibility, and sensitivity of a mass spectrometry-based proteomic method for the identification of endogenous S-nitrosylated proteins is outlined. The method enriches for either S-nitrosylated proteins or peptides through covalent binding of the cysteine sulfur with phenylmercury at pH=6.0. Phenylmercury reacts selectively and efficiently with S-nitrosocysteine since no reactivity can be documented for disulfides, sulfinic or sulfonic acids, S-glutathionylated, S-alkylated or S- sulfhydrylated cysteine residues. A specificity of 97 ± 1 % for the identification of S-nitrosocysteine peptides in mouse liver tissue is achieved by the inclusion of negative controls. The method enables the detection of 36 S-nitrosocysteine peptides starting with 5 pmoles S-nitrosocysteine/mg of total tissue protein. Both the percentage of protein molecules modified as well as the occupancy by S-nitrosylation can be determined. Overall, selective, sensitive and reproducible enrichment of S-nitrosylated proteins and peptides is achieved by the use of phenylmercury. The inclusion of appropriate negative controls secures the precise identification of endogenous S-nitrosylated sites and proteins in biological samples.